REPRESENTASI WISATA TOKO SAHABAT LINE DI KOREA SELATAN: DARI APLIKASI LINE KE PRODUK NYATA - Supriadianto, Supriadianto; Asrori, Yuni Wachid; Arintaka, Riski (Jurnal Vokasi Indonesia, 2019)
South Korea is one of the developed countries that have succeeded in developing popular culture to increase the potential for tourist visits to the country. This study aimed to investigate how Korean culture is represented in the characters displayed in the LINE application and in the visual presentation or decoration design in the LINE Friends Store so that it can be accepted globally and can attract tourists to visit the LINE Friends Store. The study was conducted with a qualitative interpretive method using the Charles Sanders Pierce’s semiotic approach. The focus of the study was to describe the representation of the signs displayed in the LINE application characters and in the decoration design or visual presentation in the LINE Friends Store using icons, indexes, and symbols. The result of the study showed that what is displayed in the LINE Friends Store can provoke consumers' interest to come and shop because the products offered there have a cultural closeness which has global characteristics and all of them are displayed in a form that emphasizes the popularity and success of modern development. The role of LINE application, whose products have been globalized, has become a very effective driving force to further popularize the LINE Friends Store tour.